ENSINO SUPERIOR: TRAJETÓRIAS E SABERES DOCENTES - Ana Paula Pereira Arantes; Raimunda Abou Gebran (Universidade do Oeste Paulista, 2012)
This research aimed at understand the trajectory and knowledge of active teachers in the Pedagogy course at a private institution (college), analyzing their formation, their concepts on education, experiences and suffered influences in order to outline a profile of teachers working in Pedagogy course. The research was developed in the qualitative approach, using the procedure as a case study. The research procedures that enabled the achievement of intended goals were questionnaires, documentary research and semi-structured interviews. Teachers participated in the study of the Pedagogy Course from a private institution in Minas Gerais. The faculty participants were selected by a core training which is structured the curriculum of the course: basic studies and further studies integrators. Selected by lot, two teachers from each core, which had more than one year of performance in the teaching pedagogy course and which have agreed toparticipate anonymously in the survey. The analysis of collected data revealed significant aspects with regard their formation and expertise, namely: absence of didactic training and preparation for teaching in higher education, the privilege of teaching and low involvement of teachers with research and extension activities, the predominance of expositive class and lack organization and development of projects and interdisciplinary. Finally we understand that teaching involves a framework of knowledge that presented itself in the classroom. This refers to the understanding that teaching is concretized through praxis, theory and practice in relation referenced on reflexivity (action-reflection-action).